Supplementary teaching materials on pollution for use in high school science classes - Garrido, Teresa P. (s.n.], 1973)
Supplementary teaching materials on pollution for use in high school science classes were developed in this study.The paper aimed to present basic information on air, water, and land, suggested activities which science teachers can utilize in their classes, and lastly, gave recommendations to the school administrator and the science teacher for more effective teaching on pollution.